Expectation Gap e o risco de auditoria - Miranda, Pedro Filipe da Cunha (2022)
The successive financial scandals that happened in the beginning of the 21st century have been affecting the credibility of the profissional auditing, making the overall expectation about auditing work a lot higher. In this context, the audit expectation gap came up and it is the difference in expectation between what people expect from the auditing work and what this work consists of. In this regard, the aim of this study is to explore what are the differences between the people and auditors' expectaction, with respect to the audit work and his responsibilities in detecting frauds and errors, and if this expectation has impact on the credibility that this type of task require. Besides that, it also aims to clarify the role of audit standards as an actor on the decrease of this expectation variation. Simultaneously, a comparison between both expectations and the auditing risk is done too as well as identifying the risks associated with the auditor's job. This study contributes to the audit expectation gap perception analysis and the society view on the auditor competence, using Portugal as the use case. In this study it was possible to find out that the clarified role of the audit standards, the public awareness about the auditing risks as well as the proactive approach regarding the general training on auditor's aptness and their work are crucial factors to reduce the overall difference in expectation. The quantitative analysis based on a poll was the adopted methodology on this study. The investigation questions were created based on the state of the art, with the goal of understanding if the literature converges with the respondents' opinions.